CONTROL SYSTEM FOR TEMPERATURE, HUMIDITY AND TIME PARAMETERS ON ZELIO SMART RELAY-BASED WATERING PROCEDURES - Arif, Irfan; Sujiwa, Akbar (BEST, 2019)
Watering plants usually done manually using human power. that has risk negligence and inaccuracy. also, in time and cost is not efficient. Another factor that can affect the quality of crops is a factor of humidity and temperature. For those reason, writers made a tool that can work according to the level of humidity and temperature automatically and continuously. This tool uses Zelio Smart Relay as automatic controller. The 808H5V5 humidity sensor and LM35 temperature sensor is used as input. The LM35 temperature sensor detect the ambient temperature, where as 808H5V5 humidity sensor detect ambient air humidity, and time of watering adapted to the Smart Relay timer. The entire sensor input is programmed using ZELIO SOFT 2. Setting the temperature and humidity when the detected 30oC and >70% as well as the timeshows at 08.30 – 09.00 am and 16.00 – 16.30 pm the pump will automatically ON.